Candidaemia in internal medicine departments: the burden of a rising problem. (15th February 2013) - Bassetti, M.; Molinari, M. P.; Mussap, M.; Viscoli, C.; Righi, E.; Roilides, E.
Abstract Although internal medicine wards (IMWs) represent a significant reservoir of patients with candidemia, few investigators have specifically addressed the epidemiological aspects of candidaemia in this population. Of all patients hospitalized during the study period with candidaemia, 133/348 (38%) were admitted to IMWs. Variables associated with IMWs included: antibiotic therapy prior to hospitalization, urinary or central venous catheter, parenteral nutrition, tumour and age >75 years. Overall, 30‐day mortality in IMWs was significantly higher than that in other wards (51.1% vs. 38.2%, p <0.02). Multiple logistic regression analysis identified the administration of antifungal treatment 48 h after having the first positive BC as an independent determinant of hospital mortality. Patients with candidaemia in IMWs account for a substantial proportion of patients with candidaemia and have higher mortality compared with patients in other wards.